Is Rumination after Bereavement Linked with Loss Avoidance? Evidence from Eye-Tracking - Eisma, Maarten C. (Public Library of Science, 2014)
Rumination is a risk factor in adjustment to bereavement. It is associated with and predicts psychopathology after loss. Yet, the function of rumination in bereavement remains unclear. In the past, researchers often assumed rumination to be a maladaptive confrontation process. However, based on cognitive avoidance theories of worry in generalised anxiety disorder (GAD) and rumination after post-traumatic stress disorder (PTSD), others have suggested that rumination may serve to avoid painful aspects of the loss, thereby contributing to complicated grief. To examine if rumination is linked with loss avoidance, an eye-tracking study was conducted with 54 bereaved individuals (27 high and 27 low ruminators). On 24 trials, participants looked for 10 seconds at a picture of the deceased and a picture of a stranger, randomly combined with negative, neutral or loss-related words. High ruminators were expected to show initial vigilance followed by subsequent disengagement for loss stimuli (i.e., picture deceased with a loss word) in the first 1500 ms. Additionally, we expected high ruminators to avoid these loss stimuli and to show attentional preference for non-loss-related negative stimuli (i.e., picture stranger with a negative word) on longer exposure durations (1500–10000 ms). Contrary to expectations, we found no evidence for an effect of rumination on vigilance and disengagement of loss stimuli in the first 1500 ms. However, in the 1500–10000 ms interval, high ruminators showed shorter gaze times for loss stimuli and longer gaze times for negative (and neutral) non-loss-related stimuli, even when controlling for depression and complicated grief symptom levels. Effects of rumination on average fixation times mirrored these findings. This suggests that rumination and loss avoidance are closely associated. A potential clinical implication is that rumination and grief complications after bereavement may be reduced through the use of exposure and acceptance-based therapeutic techniques.